2021
DOI: 10.3389/fpls.2021.616776
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Analysis of the GATA Factor HANABA TARANU Mutants in Medicago truncatula Reveals Their Roles in Nodule Formation

Abstract: Formation of nodules on legume roots results from symbiosis with rhizobial bacteria. Here, we identified two GATA transcription factors, MtHAN1 and MtHAN2, in Medicago truncatula, which are the homologs of HANABA TARANU (HAN) and HANABA TARANU LIKE in Arabidopsis thaliana. Our analysis revealed that MtHAN1 and MtHAN2 are expressed in roots and shoots including the root tip and nodule apex. We further show that MtHAN1 and MtHAN2 localize to the nucleus where they interact and that single and double loss-of-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
(85 reference statements)
0
2
0
Order By: Relevance
“…Some GATA transcription factors were shown to be involved in symbiosis development in legume plants. The MtHAN1 and MtHAN2 genes encoding GATA transcription factors in M. truncatula are mainly expressed in the nodule primordia and in the infection zone in mature nodules, suggesting the participation of these transcription factors in nodulation [ 73 ]. The expression of genes encoding NCR peptides, responsible for bacteroid differentiation, is shown to be suppressed in han1 han2 double mutant [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some GATA transcription factors were shown to be involved in symbiosis development in legume plants. The MtHAN1 and MtHAN2 genes encoding GATA transcription factors in M. truncatula are mainly expressed in the nodule primordia and in the infection zone in mature nodules, suggesting the participation of these transcription factors in nodulation [ 73 ]. The expression of genes encoding NCR peptides, responsible for bacteroid differentiation, is shown to be suppressed in han1 han2 double mutant [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a prior study reported that nodulation is adversely impacted by the NopAA mutant, and this might be due to the different genetic background of the host legume (Almeida‐Trapp & Mithöfer, 2019; Okazaki et al, 2013). Furthermore, ABA and cytokinin act antagonistically to regulate nodule initiation in the root cortex (Wang et al, 2020; Xu, Song, et al, 2021; Xu, Wang, et al, 2021). Our results support that ABA is required to initiate rhizobium infection in soybean.…”
Section: Discussionmentioning
confidence: 99%